Antibacterial activity of Ulvan from Ulva fasciata, Sri Lanka - Thenushika, J; Thenusha, J; Mayurika, M; Sivasinthujah, S; Tharmila, J; Malathy, P (Faculty of Allied Health Sciences, University of Jaffna, Sri Lanka., 2025)
Introduction: In recent years, ulvan, a sulfated water-soluble polysaccharide derived from algae, has received considerable attention for its potent antibacterial activity for wound healing. However, the antibacterial potential of Ulva fasciata from Sri Lanka has not been extensively explored, leaving a significant research gap. Objective: To extract ulvan polysaccharide from Ulva fasciata and evaluate its antimicrobial activity against Staphylococcus aureus (ATCC 25923) and Escherichia coli (ATCC 25922). Methodology: Ulva fasciata was collected from Matara, Sri Lanka. Dried Ulva fasciata powder was depigmented with hexane, followed by ethanol to remove small molecules, then heated in distilled water (1:20 w/v) at 85–90 °C for 6 h. The extract was filtered, concentrated under vacuum, and precipitated with cold ethanol to obtain crude ulvan, confirmed by FTIR-ATR. Antibacterial activity was assessed using agar well diffusion assays at concentrations of 50 mg/mL and 100 mg/mL against S. aureus and E. coli. Whereas ciprofloxacin (0.5 mg/mL) and distilled water were used as positive and negative controls, respectively. The test was replicated. Results: The yield in percentage of ulvan polysaccharide from Ulva fasciata powder was 14.032%. The appearance of stretching bands of sulfate ester at 843.74 cm-1, sulfate group at 1219.81 cm-1, and polysaccharide band at 1073.53 cm-1, along with OH stretch at 3253.11 cm-1 in the FTIR confirmed the presence of sulfated polysaccharide. Ulvan polysaccharide demonstrated antibacterial activity in a concentration-dependent manner, with 50 mg/mL producing a zone of inhibition of 13.75 mm and 22.75 mm against S. aureus and E. coli, respectively, while 100 mg/mL produced 15.75 mm and 27.75 mm, whereas the standard showed 34 mm and 38 mm, respectively. Conclusion: The extracted ulvan polysaccharide from Ulva fasciata was confirmed by FTIR analysis as a sulfated polysaccharide. It exhibited notable antibacterial activity against both S. aureus and E. coli in a concentration-dependent manner. Although its activity was lower than the standard, the results highlight its potential as a natural antibacterial agent. Further purification of the crude ulvan and determination of the MIC are recommended to validate this study.
Keywords: Antimicrobial activity; Ulvan; Ulva fasciata; Polysaccharide extraction